Stochastic models for analyzing Criminal Careers - Copas, John B. (Journal of quantitative criminology, 1988)
The recent National Research Counci! Panel on Research on Criminal Careers (Blumstein et al. , 1986) identified the following as one of its items for future research: “... changes in the model [for analyzing criminal careers] are needed to reflect the consequences of the considerable heterogeneity in the values of A.” This paper discusses the range of stochastic models available that take account of variations in A that occur during an individual offender's career, variations in A between different types of offenders, and both forms of variation simultaneously. Together these models are a flexible and powerful tool for studying criminal careers. For completeness, failure rate regression models are also briefly described.